Indigenous Research, Differing Value Systems - Foley, Dennis (The Australian Journal of Indigenous Education, 2000)
The collective aim of many of this Journal's readers is to provide Indigenous Australians with a sound education to allow us (Indigenous Australia) to take a more active role in Australian society. My personal research interest is in business studies, training Indigenous Australians in management and business principles. I continually face the question of am I training my kin in a Western science that is often at the opposite end of the spectrum to Indigenous thought and practice?